2019
DOI: 10.3390/atmos10100602
|View full text |Cite
|
Sign up to set email alerts
|

Intercomparison of the Surface Energy Partitioning in CMIP5 Simulations

Abstract: The warming climate significantly modifies the global water cycle. Global evapotranspiration has increased over the past decades, yet climate models agree on the drying trend of land surface. In this study, we conducted an intercomparison analysis of the surface energy partitioning across Coupled Model Intercomparison Phase 5 (CMIP5) simulations and evaluated its behaviour with surface temperature and soil moisture anomalies, against the theoretically derived thermodynamic formula. Different responses over lan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Land-atmosphere interaction processes, which control the surface-atmosphere exchanges of water, energy, and atmospheric carbon dioxide (CO 2 ) across the atmospheric boundary layer, play a key role in ecosystem processes, hydrologic and biogeochemical cycles, and even in weather and climate (You et al, 2017;Yang et al, 2019). Previous studies have shown that climate simulations are especially sensitive to seasonal and diurnal variations in the surface energy partitioning of available energy into sensible heat (H ) and latent heat (λE) fluxes in numerical models (Gao et al, 2004), where considerable uncertainties still remain in the land-surface parameters (Sun et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Land-atmosphere interaction processes, which control the surface-atmosphere exchanges of water, energy, and atmospheric carbon dioxide (CO 2 ) across the atmospheric boundary layer, play a key role in ecosystem processes, hydrologic and biogeochemical cycles, and even in weather and climate (You et al, 2017;Yang et al, 2019). Previous studies have shown that climate simulations are especially sensitive to seasonal and diurnal variations in the surface energy partitioning of available energy into sensible heat (H ) and latent heat (λE) fluxes in numerical models (Gao et al, 2004), where considerable uncertainties still remain in the land-surface parameters (Sun et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…However, as compared to temperature shifts, changes in global hydrological cycle (e.g. precipitation) are relatively less wellunderstood, despite the strong coupling between energy and water transport (Allen and Ingram, 2002;Marvel and Bonfils, 2013;Yang et al, 2019). Andrews et al (2010) pointed out that the precipitation response to climate change can be roughly split into a fast response part strongly correlated with radiative forcing absorbed by the atmosphere and a relatively slow response to global surface temperature change.…”
Section: Introductionmentioning
confidence: 99%